Ketimpangan Representasi Stereotipe Perempuan Dalam Ruang Publik - Sahyana, Anggi Fuja; Anggraini, Riska; Pertiwi, Adinda Putri; Karwati, Lilis (IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT: The purpose of this study is to examine various stereotypical representations of women in the public sphere. This research uses library research, as for the analysis method carried out, namely by selecting, comparing, combining, and sorting out relevant research results related to the inequality of stereotypical representation of women in public spaces, and then conclusions are drawn, so that relevance is found. The results of the research study show that women have begun to manipulate and actualize their role in various public spaces, the public spaces in question, namely politics and government, education and entertainment. Even in entertaiment the existence of females predominates compared to males. However, the reality is that women always get the advantage of actualizing themselves in various domains. Although women became dominant in the percentage of involvement of the entertaiment world, still public society gave a negative stereotypical representation for women as domestic beings who were only able to do homework, take care of children, serve their husbands, as objects of male sexuality, and figures considered weak, emotional, not credible and helpless.Keywords: women, gender, stereotypes, public